Analysis of potential interactions between vitamins D and C using gene expression profiles from mouse models - Jiao, Yan; Niu, Mingming; Tian, Cheng; Yan, Jian; Vancil, Aron W.; Yan, Xuenan; Zhang, Ming (Cellular and Molecular Biology, 2017)
Vitamin D (VD) and vitamin C (VC) have been recognized as essential elements for human health.  Animal models, especially mouse models, have been widely used in the study of VD and VC. This study is to investigate how VD and VC interact at molecular level using whole genome expression profiles from spleens of 111 mouse strains and livers from 40 mouse strains. We first identified the genes that are closely correlated to vitamin D receptor (Vdr) and gulonolactone oxidase (Lgo). We next analyzed the potential molecular pathways of Vdrand Lgo correlated genes and examined how these two sets of pathways are connected in liver and spleen. Our results indicated that Vdrand Lgo associate to distinct groups of genes. While most of genes are not the same, a few of them are associated to both Vdrand Lgo.  Our gene network construction suggests that there are interactions between Vdrand Lgopathways.  Our work laid down the foundation for future study of the interactions between VD and VC and revealed the potential bias when using animals for the study of VD or VC, as humans do not produce VC.